2000
DOI: 10.1002/1097-4628(20001107)78:6<1200::aid-app40>3.3.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polypropylene and ethylene–propylene copolymer blends for industrial applications

Abstract: The crystalline structure and physico-mechanical properties of polypropylene (PP) blended with ethylene-propylene copolymer (EPM) were investigated. WAXS diffractograms showed that the addition of EPM did not affect the crystalline structure of PP. DSC curves revealed the presence of two T g peaks indicating the amorphous phases of EPM and PP. As EPM increased, the elastomeric domains cavitated from PP matrix increased while the tensile stress and modulus of elasticity decreased. Impact strength, on the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…This effect is less pronounced for PP5341, probably because of an already large amount of fibrils. Figure 7b shows that the addition of 20 wt% random copolymer reduces the tensile strength and increases the elongation at break, confirming the finding of Nitta et al (2005); and Bedia et al (2000). No yielding in the mechanical responses along MD is seen, possibly due to a strong fibril structure of the stretched films (Sadeghi and Carreau, 2008a).…”
Section: Resultssupporting
confidence: 77%
“…This effect is less pronounced for PP5341, probably because of an already large amount of fibrils. Figure 7b shows that the addition of 20 wt% random copolymer reduces the tensile strength and increases the elongation at break, confirming the finding of Nitta et al (2005); and Bedia et al (2000). No yielding in the mechanical responses along MD is seen, possibly due to a strong fibril structure of the stretched films (Sadeghi and Carreau, 2008a).…”
Section: Resultssupporting
confidence: 77%
“…Therefore, the general trend is significant, but individual points are not significant. This relationship has also been observed for PP/EPR blends 69. It is due to the thickening of amorphous layers between lamellae, which is caused by the increased amorphous content of the PP‐ g ‐EPR.…”
Section: Resultssupporting
confidence: 62%
“…The EPR in PP/EPR blends does not usually affect the T m of the PP 40, 68, 70. However, Bedia et al reported a decrease in T m of 2.8°C from homoPP to a 50% EPR blend 69. The lack of change in T m suggests that the incorporation of EPR does not affect lamellar thickness.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, the size of the rubber particles is decreased when the grafted polymers are added to the blend, in particular, in blends containing both functionalized polymers, this being one of the aspects responsible for the better impact behavior. Bedia et al 35 demonstrated that, as the EPR content increases, the rubber domain dispersed in the continuous matrix increases, this effect being particularly evident at concentrations above 40% of EPR in the blend. On the other hand, they observed that the highest impact strength was obtained at 40% EPR and starts to decrease for higher concentrations.…”
Section: Morphological Analysismentioning
confidence: 99%